Impact of pulmonary veins anatomy on outcome of cryoablation or radiofrequency catheter ablation for atrial fibrillation. (24th May 2021) - Silva, G; Queiros, P; Silva, M; Teixeira, R; Almeida, J; Fonseca, P; Oliveira, M; Goncalves, H; Primo, J; Fontes-Carvalho, R
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND Pulmonary vein isolation is the cornerstone of interventional treatment of atrial fibrillation (AF). Pulmonary veins frequently display anatomic variants. If this influences the recurrence of AF after catheter ablation is still a matter of debate. PURPOSE Our aim was to determine if pulmonary vein anatomy variants influences the recurrence of AF after catheter ablation with radiofrequency or cryoablation. METHODS Retrospective analysis of patients with paroxysmal or persistent atrial fibrillation who underwent pulmonary vein isolation by radiofrequency (RF) or cryoablation (CA) in a single center between January 2017 and September 2019. All patients underwent computed tomography before AF ablation. Within each treatment group (RF or CA), patients were stratified according to their PV anatomy in: regular (2 left PVs and 2 right PVs) or variant (left common trunk, right common trunk, bilateral common trunk, right intermediate branch or other). The primary end-point was 1-year recurrence of AF. Recurrence was defined as electrical documented AF. RESULTS A total of 425 patients (RF = 300 and CA = 125), aged 56.6 ± 11.7 years, 277 men (65.0%) were enrolled. The majority of patients had paroxysmal AF (n = 343, 81.5%). Mean CHA2DS2-VASc score was 1.12 ± 1.28. Regular PV anatomy was identified in 357 patients (84.0%), a left common trunk in 53 patients (12.5%), a bilateral common trunk in 5 patients (1.2%), a right intermediate branch in 3 patients (0.7%) and other mixed variants in 7 patients (1.6%). There were no significant differences in the baseline clinical and echocardiographic characteristics between groups. At 1-year follow-up, patients with atypical PV anatomy had more AF recurrence (regular 8.1% vs variant 16.2%; p = 0.037). Analyzing according to the ablation technique there was no difference in AF recurrence between PV anatomy groups in patients submitted to radiofrequency (regular 8.3% vs variant 13.0%; p = 0.224). On the other hand, in cryoablation group, patients with PV anatomic variant had significantly higher rates of 1-year AF recurrence (regular 7.8% vs variant 22.8%; p= 0.033). CONCLUSION: The presence of atypical PVs anatomy seems to be associated with higher rates of AF recurrence at 1-year in patients undergoing cryoablation. Further prospective studies are needed to confirm the PV anatomy impact in the success of the procedure and if this needs to be accounted in the choice of ablation technique.